Assessment of Financial Literacy among Nepalese Youth - Puri, Aliza (Nepalese Journal of Finance, 2025)
The study examines the impacts of financial literacy among Nepalese youths. Attitude towards financial literacy is the dependent variables. The selected independent variables friend circle, family background, academic education, financial courses and social media. The primary source of data is used to assess the opinions of respondents regarding friend circle, family background, academic education, financial courses and social media and attitude of youths towards financial literacy. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and impacts of financial literacy among Nepalese youth. The study showed that friend circle is positively correlated to attitude towards financial literacy. It indicates that friend circle leads to an increase in attitude towards financial literacy. Likewise, family background is positively correlated to attitude towards financial literacy. It indicates that family background has a positive impact on attitude towards financial literacy. Further, academic education is positively correlated to attitude towards financial literacy. It indicates that academic education leads to an increase in attitude towards financial literacy. Additionally, financial courses and social media also demonstrate positive correlations with attitude towards financial literacy suggesting their significant roles in shaping the financial literacy among Nepalese youth.